Modelling of the availability for the ship integrated control system sensors - Ioannis K. Dagkinis; Panagiotis M. Psomas; Agapios N. Platis; Branislav Dragović; Nikitas V. Nikitakos (Cleaner Logistics and Supply Chain)
Innovative control systems regulate and adjust a lot of operational conditions of the modern ship’s functions. A comprehensive Ship Integrated Control System (SICS), for the operation of the propulsion plant, the power management of the auxiliary engines, the operation of the auxiliary machinery, the loading and unloading of cargo, the navigation, the management of maintenance and the purchase of spare parts is implemented in the paper. A strategy where preventive maintenance is carried out and different repair actions can be considered is proposed. The SICS is subjected to various levels of degradation, and if so, a repair process will be undertaken to restore the system to its full working state. The aim of the paper is to optimize the best strategy for the different sensors of the SICS where only maintenance actions are performed or only repair actions need to be carried out. The model is developed and applied to the sensors of a ship and the objective is to determine the optimal asymptotic availability, and in particular in the main propulsion plant of a Liquefied Natural Gas (LNG) carrier. The model is illustrated by a numerical example based on empirical data.